Effect of Four Bleaching Regimens on Color Changes and Microhardness of Dental Nanofilled Composite - Simone Xavier Silva Costa; Anne Buss Becker; Alessandra Nara de Souza Rastelli; Leonor de Castro Monteiro Loffredo; Marcelo Ferrarezi de Andrade; Vanderlei Salvador Bagnato (Hindawi Limited, 2009)
Objective. The purpose of this study was to compare the color changes and microhardness of a nanocomposite after four bleaching regimens. Materials. Twenty-five specimens (n=25) were made with a nanocomposite resin (Filtek Supreme XT). The specimens were divided into five groups equally (n=5): bleaching groups and control group, as follows: G1: artificial saliva at 37∘C; (control) G2: hydrogen peroxide (HP) at 7%; G3: hydrogen peroxide (HP) at 35%; G4: carbamide peroxide (CP) at 10%; G5: carbamide peroxide (CP) 35%. Color measurements were made with spectrophotometer using CIELAB color scale. The Vickers hardness (VHN) measurements were performed at the top surface. The data were analyzed with two-way Analysis of Variance. Results. ΔE and VHN mean values into the groups were not statistically different, however, the VHN mean values before and after storage and bleaching showed statistically significant differences. Conclusion. Nanocomposite samples showed no significant alteration (color and microhardness) after bleaching. Thus, no replacement of restorations is required after bleaching.